2012
DOI: 10.1149/2.096205jes
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Scale Modeling of Li-Ion Batteries: Parameterization and Validation

Abstract: A fully parameterized microscale model for lithium ion cells is presented in which the solid and pores (filled by electrolyte) are spatially resolved, and the mass and charge transport equations describing diffusion and migration in each phase are solved separately. Such a model allows: (1) the correlation of structure-scale, non-homogeneous material properties with macroscopic battery performance, and (2) the correlation of geometrical electrode morphology with macroscopic battery performance (electrode desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
135
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 53 publications
0
135
0
1
Order By: Relevance
“…30,42,43 As shown schematically in Figure 2a, the simulation environment consists of a porous, three-dimensional electrode microstructure, a 13 μm thick homogenized separator, and a one-voxel thick counter electrode made of pure, non-porous lithium. The pores are filled with electrolyte.…”
mentioning
confidence: 99%
“…30,42,43 As shown schematically in Figure 2a, the simulation environment consists of a porous, three-dimensional electrode microstructure, a 13 μm thick homogenized separator, and a one-voxel thick counter electrode made of pure, non-porous lithium. The pores are filled with electrolyte.…”
mentioning
confidence: 99%
“…[18][19][20] Wiedemann et al 19 clearly demonstrated how the complex shape of reconstructed particles changed the electrochemical behavior over more simplistic spherical representations. The effect of aniostropic diffusion of lithium through the particle has also been studied.…”
mentioning
confidence: 99%
“…In the second example, we investigate crack initiation and propagation under potentiostatic charging of LiMn 2 O 4 cathodic electrode particle. A two dimensional realistic particle geometry is depicted from SEM micrograph presented in [6] and analysed under plain-strain conditions. The particle size is around ≈ 10µm.…”
Section: Results and Conclusionmentioning
confidence: 99%